Competency and Performance of Physical Education Teachers for Elementary School in Semarang Indonesia - Mugiyo Hartono; Atip Nurcahyani; Wahyu Ragil Kurniawan; Andry Akhiruyanto (Yayasan Keluarga Guru Mandiri, 2024)
Mastering the basic competencies of a physical education teacher is one of the keys to learning. This research aims to determine how to achieve the competency of elementary school physical education teachers spread across the city of Semarang. The method used in this research was a qualitative method with an interaction analysis model and supported by the presentation of percentages. This research involved 20 elementary school physical education teachers spread across Semarang. Data analysis was carried out using data collection techniques, data reduction, data display, and drawing conclusions. The overall interview results were reduced, and the data was presented as a percentage of teacher achievement in pedagogical competence of 80% in the good category. Personality and social competency have the same value, 50%, in the good category, and professional competence results were obtained at 70% in the good category. It is concluded that harmonization is needed to master basic teacher competencies. This study contributes to all researchers interested in developing physical education teacher competence to create new models and strategies to support them in increasing their teacher competencies.